Metabolome and Transcriptome Analysis Revealed the Basis of the Difference in Antioxidant Capacity in Different Tissues of Citrus reticulata 'Ponkan' - Xiao Liang; Huixin Wang; Wanhua Xu; Xiaojuan Liu; Chenning Zhao; Jiebiao Chen; Dengliang Wang; Shuting Xu; Jinping Cao; Chongde Sun; Yue Wang (MDPI AG, 2024)
Citrus is an important type of fruit, with antioxidant bioactivity. However, the variations in the antioxidant ability of different tissues in citrus and its metabolic and molecular basis remain unclear. Here, we assessed the antioxidant capacities of 12 tissues from Citrus reticulata 'Ponkan', finding that young leaves and root exhibited the strongest antioxidant capacity. Secondary metabolites accumulated differentially in parts of the citrus plant, of which flavonoids were enriched in stem, leaf, and flavedo; phenolic acids were enriched in the albedo, while coumarins were enriched in the root, potentially explaining the higher antioxidant capacities of these tissues. The spatially specific accumulation of metabolites was related to the expression levels of biosynthesis-related genes such as chalcone synthase (CHS), chalcone isomerase (CHI), flavone synthase (FNS), O-methyltransferase (OMT), flavonoid-3'-hydroxylase (F3'H), flavonoid-6/8-hydroxylase (F6/8H), p-coumaroyl CoA 2'-hydroxylase (C2'H), and prenyltransferase (PT), among others, in the phenylpropane pathway. Weighted gene co-expression network analysis (WGCNA) identified modules associated with flavonoids and coumarin content, among which we identified an OMT involved in coumarin O-methylation, and related transcription factors were predicted. Our study identifies key genes and metabolites influencing the antioxidant capacity of citrus, which could contribute to the enhanced understanding and utilization of bioactive citrus components.